Toxicity effects of fish histopathology on copper accumulation - Padrilah S.N.; Sabullah M.K.; Shukor M.Y.A.; Yasid N.A.; Shamaan N.A.; Ahmad S.A. (Universiti Putra Malaysia, 2024)
Indexed by SCOPUS/ERA